Pelatihan Service Excellent pada Ibu-Ibu Wirausaha di RT.08 RW.19 Sendangmulyo - Semarang - Rusmalia Dewi; Yudi Kurniawan; Gusti Yuli Asih (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The aim of this community service is to provide training on Service Excellence to entrepreneurial mothers in RT.08 RW.19 to increase their understanding of the challenges, skills and competencies needed to succeed in service. Customer service requires speed, awareness about e-commerce with technology support to face increasingly difficult challenges. Good service improves business reputation. This training will discuss how to improve participants' skills for reliable customer service. Initial observations made showed that most of the women on Rt.08 Rw.19 were entrepreneurs by opening stalls or shops but providing minimal service to customers. This makes the business less developed because customers buy products because they need it, not because there is something more to the business of these entrepreneurial women. This lack of knowledge about providing excellent service to customers made the team want to help find solutions for developing the business of entrepreneurial women RT.08 Rw.19 through Excellent Service Training. The process is that these entrepreneurial women gather in the RT.08 hall and provide material on understanding and practice about Excellent Service in the form of lectures, stories and games as well as joint discussions. It is hoped that the service team for these entrepreneurial mothers will be able to understand the results of the training. By increasing their understanding of Service Excellent, they can improve the abilities of these entrepreneurial mothers to be even better at serving customers, so that they can increase their sales turnover.